A student is trying to solve the set of two equations given below:

Equation A: x + z = 6
Equation B: 3x + 2z = 1

Which of the following is a possible step used in eliminating the z-term?
Multiply equation A by −2.
Multiply equation B by 2.
Multiply equation A by 3.
Multiply equation B by 3.

Respuesta :

a possible step used in eliminating the z-term is "multiply equation A by −2."

x + z = 6
3x + 2z = 1

x + z = 6 / *(-2)
3x + 2z = 1


-2x - 2z = -12
3x+ 2z = 1

-2x + 3x -2z +2z = -12 +1
x = -11

-11 + z = 6
z = 6 + 11
z = 17

Answer:Multiply equation A by -2 is correct everyone

Step-by-step explanation:

I just took the test and checked;)

Ver imagen melissaa7
ACCESS MORE